The Effect of Conventional Method on the Length of Treatment Days for Children Underwent Circumcision at Poniran Khitan Centre Bengkulu - Ferasinta1 , Andri Kusuma Wijaya1 , Desri Suryani2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Circumcision is a minor surgical procedure that is most widely performed in the world,namely a method of cutting all or part of the prepuce of the penis for specific indications and purposes.Study Design:This study was used one-group pretest-posttest pre-experimental research design, with a totalsample 15 respondents.Results: Based on the results of the bivariate analysis using the Dependent T test, it was found that therewas an effect conventional method with a value (p value = 0, 000) on the on the length of days of care forcircumcision wounds in children undergoing circumcision at the Poniran Khitan Centre Bengkulu.Conclusion: The role of the Poniran Khitan Center will greatly assist in facilitating children in treatingwounds who undergo circumcision